2020
DOI: 10.1016/j.cgh.2019.06.042
|View full text |Cite
|
Sign up to set email alerts
|

Hormone Therapy for Cancer Is a Risk Factor for Relapse of Inflammatory Bowel Diseases

Abstract: Background & Aims: Exposure to hormone contraception has been associated with an increased risk of relapse of inflammatory bowel diseases (IBD). Little is known about the effects of cancer therapies, specifically hormone therapies, on the course of IBD. Methods: We conducted a retrospective cohort study, collecting data from 5 medical centers on patients with IBD who received a subsequent diagnosis of breast or prostate cancer from 1997 through 2018. For patients with q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…52 These findings are in contrast to a larger, multicenter retrospective study of both men and women with IBD that demonstrated a twofold increased risk of IBD flare associated with hormone therapy following a diagnosis of prostate or breast cancer. 53 Unfortunately, the risk was not reported separately among men versus women. The data regarding the role of male sex hormones in IBD pathogenesis and disease course are sparse and warrant investigation.…”
Section: Sex-based Differences In Ibd Clinical Presentationmentioning
confidence: 99%
“…52 These findings are in contrast to a larger, multicenter retrospective study of both men and women with IBD that demonstrated a twofold increased risk of IBD flare associated with hormone therapy following a diagnosis of prostate or breast cancer. 53 Unfortunately, the risk was not reported separately among men versus women. The data regarding the role of male sex hormones in IBD pathogenesis and disease course are sparse and warrant investigation.…”
Section: Sex-based Differences In Ibd Clinical Presentationmentioning
confidence: 99%
“…In the setting of cytotoxic chemotherapy use, cessation of IBD immunosuppression (excluding gut-selective agents such as vedolizumab for non-GI cancers) is generally recommended and indeed may not be required given the potential benefit of cytotoxic chemotherapy for IBD activity. 7 Timing of the resumption of IBD therapy following completion of therapy requires consideration on an individual basis.…”
Section: Malignancymentioning
confidence: 99%
“…The management of IBD in the setting of a current cancer may be more challenging and is influenced by the severity of IBD activity, the cancer therapy, and the individual's overall prognosis and quality of life. In the setting of cytotoxic chemotherapy use, cessation of IBD immunosuppression (excluding gut‐selective agents such as vedolizumab for non‐GI cancers) is generally recommended and indeed may not be required given the potential benefit of cytotoxic chemotherapy for IBD activity 7 . Timing of the resumption of IBD therapy following completion of therapy requires consideration on an individual basis.…”
Section: Malignancymentioning
confidence: 99%
“…Thiopurines remain the culprit with non-melanotic skin cancer (Peyrin-Biroulet et al 2011) and lymphoma (Beaugerie et al 2009). There is an increased IBD relapse rate associated with hormonal therapy in breast or prostate cancer (Axelrad et al 2019).…”
Section: Cancermentioning
confidence: 99%